ultraMEDIS – Ultra-Wideband Sensing in Medicine - Hilger, Ingrid; Dahlke, Katja; Rimkus, Gabriella; Geyer, Christiane; Seifert, Frank; Kosch, Olaf; Thiel, Florian; Hein, Matthias; Clemente, Francesco Scotto di; Schwarz, Ulrich; Helbig, Marko; Sachs, Jürgen (IntechOpen, 2013)
None